How STF allows trivial overlap of I/O and computations on Forward RTM - Colle, Pedro Henrique Boniatti; Schnorr, Lucas Mello (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2026: Anais da XXVI Escola Regional de Alto Desempenho da Região SulDO - 10.5753/eradrs.2026.21467, 2026)
With the evermore complex ecosystem of High Performance Computing (HPC), the Sequential Task Flow (STF) model arrives to provide a convenient interface to compute in heterogeneous architectures. This paper presents Star-Fletcher, a Reverse Time Migration (RTM) program implemented using STF alongside time tiling which resulted in the side effect of complete I/O to disk masking.